Development trajectory, emission profile, and policy actions: Thailand - Qwanruedee Chotichanathawewong; Natapol Thongplew (Asian Development Bank Institute (ADBI), 2012)
In Thailand climate change has been integrated into the formulation of several national plans and policies. Even though Thailand is not obligated to reduce greenhouse gas emissions, it voluntarily takes numerous actions to mitigate emissions. Both the public and private sector have been actively involved in reducing greenhouse gas emissions, with a series of measures and actions implemented in each sector. The development of renewable energy and the promotion of energy conservation and efficiency are the primary means to mitigate greenhouse gas emissions in Thailand. With the establishment of the Energy Conservation Program in 1995, a viable movement for energy conservation and efficiency and renewable energy had begun. Over the years, progress in renewable energy and energy efficiency has been made. Recently, the 15-Year Renewable Energy Development Plan and the 20-Year Energy Conservation Plan comprised several innovative measures and incentive mechanisms to further advance the development of energy efficiency and renewable energy. Regardless of government policies and measures, the private sector has also taken part in greenhouse gas emissions mitigation by implementing a number of activities to reduce carbon sources (e.g., improved production processes and resource efficiency) and to create carbon sinks (e.g., reforestation and mangrove plantations). Thailand has made significant progresses toward green and low-carbon development; however, there is a need to further address the issue. The country has to focus on the implementation of no-regret policies to ensure the decoupling of economic growth, while starting to look further at implementing least-cost policies. There should be short-term policies to immediately address a rapid increase of greenhouse gas emissions and long-term policies to address fundamental changes towards a green and low-carbon society.
Keywords: Q54; Q58; 330; climate change; thailand; greenhouse gas emissions; renewable energy; low-carbon development; Klimawandel; Wirtschaftliche Anpassung; Energieeinsparung; Förderung erneuerbarer Energien; Umweltschutz; Thailand